Transforming Civil Servant Disciplinary Law in Indonesia: From Administrative Formality to an Integrated Corruption Prevention Instrument - Moh Ibnu Ichwanusshofa; Ahmad Redi (Indonesian Journal Publisher, 2026)
The primary objective of this study is to analyze the legal transformation in the enforcement of civil servant discipline as an integrated instrument for the prevention of corruption. Corruption within the bureaucracy cannot be separated from disciplinary violations that are often treated merely as administrative formalities. Although regulated under Law Number 20 of 2023 on State Civil Apparatus and Government Regulation Number 94 of 2021 on Civil Servant Discipline, the enforcement of discipline still tends to be reactive and oriented toward individual sanctions, and has not functioned effectively as an early detection mechanism for potential corruption. This research employs a normative legal method using statutory, conceptual, and theoretical approaches. The analysis draws on the Broken Windows Theory and the Normalization of Deviance theory to explain how tolerance toward minor administrative violations may evolve into more complex forms of corruption. In addition, the legal system theory is applied to examine the interaction between legal substance, structure, and culture in the enforcement of civil servant discipline. The findings indicate that the primary weakness lies in the existing legal construction, which has not integrated disciplinary enforcement with a comprehensive corruption prevention system, along with the limited role of direct supervisors in monitoring and controlling bureaucratic behavior. This condition calls for the reconstruction of legal norms toward a more proactive and detective model of disciplinary enforcement, as well as the strengthening of administrative accountability of direct supervisors as part of an integrated corruption prevention effort.